Interdisciplinary and Child-Friendly Communication (Human Rights – Children’s Rights, 2025)
CEA Publishing’s ‘Human Rights – Children’s Rights’ book series is inspired by the idea that the universality and indivisibility of human rights can still accommodate a regional perspective on human rights protection. Different collective identities, sensitivities, and historical backgrounds may lead to different emphases on certain human rights issues, reflecting the cultural and legal heritage of Central and Eastern Europe. Although the series is primarily law-focused, it also embraces an interdisciplinary approach and therefore includes contributions from other academic fields. The main areas of law covered in the series are human rights, children’s rights, and the rule of law, as well as other areas of law that help ensure their effective implementation. A prominent feature of the series is its examination of the legal systems and jurisprudence of Central and Eastern European countries, though not exclusively so. As the series aims to provide useful legal knowledge to non-lawyers, it also offers general legal background necessary to understand the subject matter. The series is divided into two distinct sub-series, each numbered separately. One sub-series is entitled ‘Human Rights and Rule of Law’ (HRRL) and the other ‘International and Comparative Children’s Rights’ (ICCR). Regarding their relationship, HRRL is considered the more general sub-series, while ICCR focuses on more specific themes.